The art of telling and painting our own history (2014)
Starting up with a research on the chumbe belts woven by Inga women to wrap the stomach, Benjamin Jacanamijoy explored the transformational potentialities of weaving by creating new surfaces and volumes wrapped in designs. His experimenting with materials, colors, forms and textures brings together female knowledges and male thoughts of yage healing, thus turning his works of art into colorful vehicles to travel across the city telling Inga people´s own history.